2018
DOI: 10.1038/s41556-017-0033-8
|View full text |Cite
|
Sign up to set email alerts
|

The mTOR–S6K pathway links growth signalling to DNA damage response by targeting RNF168

Abstract: Growth signals, such as extracellular nutrients and growth factors, have significant impacts on genome integrity, while the direct underlying link remains unclear. Here we show that the mechanistic target of rapamycin (mTOR)-ribosomal S6 kinase (S6K) pathway, a central regulator of growth signaling, phosphorylates RNF168 at Ser60 to inhibit its E3 ligase activity, accelerate its proteolysis, and impair its function in DNA damage response, leading to accumulated unrepaired DNA and genome instability. Moreover, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
88
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(92 citation statements)
references
References 53 publications
4
88
0
Order By: Relevance
“…Furthermore, mTORC1-dependent phosphorylation of the transcription factor TFEB promotes association of TFEB with members of the 14-3-3 family of proteins, thereby forcing its retention in the cytosol (88). However, the network connecting the mTOR pathway to the DNA damage response continues to be elucidated (92)(93)(94)(95). A recent study (95) showed that mTOR/S6K signaling leads to phosphorylation and subsequent degradation of RNF168, and hyperactivation of mTOR via LKB1 leads to decreased levels of RNF168 and increases DNA damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, mTORC1-dependent phosphorylation of the transcription factor TFEB promotes association of TFEB with members of the 14-3-3 family of proteins, thereby forcing its retention in the cytosol (88). However, the network connecting the mTOR pathway to the DNA damage response continues to be elucidated (92)(93)(94)(95). A recent study (95) showed that mTOR/S6K signaling leads to phosphorylation and subsequent degradation of RNF168, and hyperactivation of mTOR via LKB1 leads to decreased levels of RNF168 and increases DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…However, the network connecting the mTOR pathway to the DNA damage response continues to be elucidated (92)(93)(94)(95). A recent study (95) showed that mTOR/S6K signaling leads to phosphorylation and subsequent degradation of RNF168, and hyperactivation of mTOR via LKB1 leads to decreased levels of RNF168 and increases DNA damage. One possible explanation for our observed results is that mTOR (or one of its downstream targets) could directly phosphorylate polκ and thereby affect its localization as has been shown for other proteins that undergo nuclear-cytoplasmic shuttling (96)(97)(98)(99).…”
Section: Discussionmentioning
confidence: 99%
“…Our recent study has demonstrated that mTORC1-S6K pathway can inhibit DDR through phosphorylating RNF168 at Ser60 by impairing its E3 ligase activity and promoting TRIP12-dependent RNF168 degradation. Importantly, ectopic expression of phosphorylation-resistant mutant, RNF168-S60A, rescues DNA damage defects and inhibits Lkb1 deletion (causing hyper-activation of mTORC1-S6K pathway)-induced lung tumor development (Xie et al 2018) (Fig. 1b).…”
Section: Mtor Signaling and Ddrmentioning
confidence: 98%
“…Hyperactivation of TORC1 has been linked to defects in the DNA damage response in single celled and multicellular organisms (Begley, Rosenbach, Ideker, & Samson, 2004;Feng et al, 2007;Klermund, Bender, & Luke, 2014;Ma, Vassetzky, & Dokudovskaya, 2018;Pai et al, 2016;Xie et al, 2018). The observation that meiotic DSBs promote the GATOR1 dependent downregulation of TORC1 activity during Drosophila oogenesis, suggested the low TORC1 activity may be important to the regulation of meiotic DSB.…”
Section: Gator1 and Tsc Promote The Repair Of Meiotic Dsbsmentioning
confidence: 99%